Random Curves Journeys of a Mathematician - Koblitz, Neal (Springer Berlin Heidelberg : Imprint: Springer, 2008)
These autobiographical memoirs of Neal Koblitz, coinventor of one of the two most popular forms of encryption and digital signature, cover many topics besides his own personal career in mathematics and cryptography - travels to the Soviet Union, Latin America, Vietnam and elsewhere, political activism, and academic controversies relating to math education, the C. P. Snow two-culture problem, and mistreatment of women in academia. The stories speak for themselves and reflect the experiences of a student and later a scientist caught up in the tumultuous events of his generation.